Behavioral Determinants and their Impacts on Customers’ Saving Deposits in Islamic Banks - Zakiah, Farah; Al-Aidaros, Al-Hasan (International Journal of Economics and Financial Issues, 2016)
The purpose of this paper is to determine the factors that affect Islamic ethical behavior of customers in Malaysian Islamic banking sector. A survey has been conducted by using questionnaire that was adopted and created. The data from 530 respondents were collected from customers of Islamic banks located in Malaysia. The study reveals that there were differences between age, marital status and income based on the independent sample t- test and one -way ANOVA analysis of the demographic factors while there was no difference for race, gender and educational level. The regression analysis indicates a significant positive relationship between religious obligation and reputation with the Islamic ethical behavior of Malaysian customers. Conversely, profit and investment shows insignificant effect on the Islamic ethical behavior of Malaysian customers. The paper contributes to the literature on Islamic Banking in South East Asia economy. Keywords: Malaysia, Islamic Ethical Behavior, Islamic banks JEL Classifications: C0, J1